Respostas

2014-08-03T19:04:43-03:00
A) 3x² + 9x - 12=0
Δ= b² - 4 ac
Δ= 9² - 4 . 3. (-12)
Δ= 81 + 144
Δ= 225

x= -b +/- √Δ / 2a
x= - 9 +/- √225 / 2.3
x= -9 + 15 /6
x'= 6 /6
x'= 1

x''= -9 -15 / 6
x''= - 24 /6
x''= - 4



1 1 1
2014-08-03T21:08:05-03:00
A) 3x² + 9x - 12 = 0
a= 3  b=9  c=-12
▲= b² - 4. a. c
▲= 9² - 4. 3. (-12)
▲= 81 + 144
▲= 225
x= -b ± √▲ tudo dividido por 2.a = 2.3
x= -9 ± 15 tudo dividido por 6
x¹ = -9 - 15 tudo dividido por 6 = -24/6 = -4
x² = -9 + 15 tudo dividido por 6 = 6/6 = 1

S={-4, 1}

x²+10-24=0
x² - 14 = 0
x² = 14
x = 
√14
x = ±√14
x= -√14 ou +√14